Metode Audiolingual Dalam Pembelajaran Bahasa Arab - Budi Santoso Wibowo; Irfan Irfan (Departement of Mathematics Education, 2024)
The Audiolingual method was first introduced in 1964 by Nelson Broos. This method revolutionized language teaching by changing it from just a scientific language learning method, the result of a combination of principles and views of structural linguistics, behavioral psychology, and contrastive analysis. This research is library research. Library research is an argumentative disclosure of data sources in the form of studies. The results of this research reveal that the Audiolingual method is based on the assumption that language is, first of all, speech. Therefore, learning Arabic must begin with listening to the sounds of the language in the form of words or sentences and then pronouncing them before learning reading and writing skills. This method revolutionized language teaching by changing it from just a scientific language learning method, the result of a combination of principles and views of structural linguistics, behavioral psychology, and contrastive analysis.